Islamic Education Based on Higher Order Thinking Skills (HOTS) in The Perspective of Neuroscience - Prihantoro, Wahyu Kholis; Suyadi, Suyadi (Universitas Ahmad Dahlan, 2021)
Education is not only the process of transferring knowledge. Then a student is asked to memorize, then is assessed based on the ability to memorize that knowledge. At the same time, a student at this time needs to have high-level thinking skills or HOTS. The launching and recommendation of the application of HOTS in the learning process is one of the strategic efforts to improve learning capacity, especially the learning of religious education in the HOTS of critical thinking. Logically, the problem of higk level thinking, which is the person's cognitive skills, is the upper front part, which is called the prefrontal cortex. The brain part of this part is known as the center of ecretutive control, or the student is a high-level thinking. Also, place of problem solving, regulation, create character and personality. Sciences strategic activities are carried out in Islamic Education so that they can get high-level ability to be enhanced with the HOTS indicator: (1) analysis level, (2) evaluation level, (3) level of integration. This research enriched scientific knowledge in other studies.